Potensial Risk of Type 2 Diabetes Mellitus - Ema Mayasari (Journal of Global Research in Public Health, 2024)
Type 2 Diabetes Mellitus (Type 2 DM) is a chronic disease also called kencing manis which is caused by a metabolic disorder characterized by an increase in blood sugar due to a decrease in insulin secretion by pancreatic beta cells or due to impaired insulin function (insulin resistance). There are several factors that are a potential risk of DM disease that are inherent in the individual and also their lifestyle. This study aims to analyze the potential risks of diabetes mellitus. The research design was case control with 54 respondents consisting of 27 case groups and 27 control groups. Data collection was carried out by interviews at each respondent's home.  Data were analyzed using a measure of the relationship between exposure (risk factors) and disease incidence which is called Odd Ratio (OR) analysis or what is called opportunity analysis. Individuals with a habit of consuming sweet foods have a 1.39 times greater risk of developing Type 2 DM compared to those who rarely consume sweet foods. Individuals with a habit of rarely exercising have a 4.73 times greater risk of developing Type 2 DM compared to those who have a habit of exercising regularly. And individuals with a nuclear family history of suffering from DM have a 6.25 times greater risk of developing Type 2 DM compared to those who do not have a nuclear family history of suffering from DM. Type 2 DM can be caused by people's consumption patterns, one of which is the habit of consuming sweet foods or foods that contain high levels of glucose. Other causes are physical activity habits, including exercise habits, and family history, which are factors that can cause Type 2 DM.